Analisis Kebijakan Penanggulangan Kekerasan terhadap Anak di Masa Pandemi Covid-19 - Rusliandy Rusliandy; Ade Risna Sari; Burhanuddin Burhanuddin; Syahwami Syahwami; Yayat Suharyat (Jurnal EL-RIYASAH, 2022)
Cases of violence against children during the Covid-19 Pandemic are increasing. Therefore, it is necessary to analyze an appropriate policy to overcome it. The purpose of this paper is to conduct a policy analysis of the problem of violence against children carried out by the population control service, family planning, women's empowerment and child protection in order to obtain policy recommendations to minimize these problems. The data collection method used in this research uses literature study techniques. The author collects various journals, research reports and news related to violence against children. There are several alternative policies that have been formulated, namely prevention and education campaign policies, policies for establishing a child protection task force and policies for developing children's help line services for child protection. Meanwhile, the policy recommendations formulated are kids help line service policies. This policy will be able to develop mechanisms for prevention, early detection and reporting of violence against children. So that in the end this policy will increase social supervision of children. Cases of violence against children are increasing every year. Therefore, appropriate policy interventions are needed to overcome them. The findings of this study included several alternative policies that were formulated, namely the policy of prevention and education campaigns, the policy of establishing a task force for child protection, educational activities in women-friendly spaces, (b) meetings with village government, traditional leaders and community leaders to synergize prevention and treatment efforts. cases of violence against women, (c) family economic development